COMPONENTS AND THEMATIC GROUPS OF INTERNET TERMS (Academia Science Repository, 2023)
This scientific article presents the thematic groups of Internet terms and their main contents. The article also emphasizes the use and meaning of these terms. Reliable sources are relied upon to provide information.